The Possibility of Wide Area Evacuation in the Event of Natural Disasters: A Survey in Amagasaki City, Hyogo Prefecture - Sawada, Masahiro; Sato, Takao (Journal of disaster research, 2024)
In industrial clusters that are affected by earthquakes and tsunamis, advance countermeasures are necessary to ensure the continuity of business operations of companies. This article presents the results of a questionnaire survey of small- and medium-sized enterprises in Amagasaki City, Hyogo Prefecture, to determine the current status of disaster countermeasures, and a questionnaire survey of residents’ awareness of risks and their current countermeasures.